Larvicidal and pupicidal evaluation of silver nanoparticles synthesized using Aquilaria sinensis and Pogostemon cablin essential oils against dengue and zika viruses vector Aedes albopictus mosquito and its histopathological analysis. (18th August 2018) - Ga'al, Hassan; Fouad, Hatem; Mao, Guofeng; Tian, Jiaxin; Jianchu, Mo
Abstract: Mosquitoes pose a threat to humans and animals, causing millions of deaths every year. Vector control by effective eco-friendly pesticides of natural origin is a serious issue that requires urgent attention. The employment of green-reducing extracts for nanoparticles biosynthesis in a rapid and single-step process represents a promising strategy. In this study, silver nanoparticles (AgNPs) were biofabricated using an essential oil of Aquilaria sinensis (AsEO) and Pogostemonis Herba essential oil of Pogostemon cablin (PcEO) in one step and cost-effective manner. UV–vis spectrophotometry, Fourier transform infrared spectroscopy, scanning electron microscopy, transmission electron microscopy, X-ray diffraction analysis and energy-dispersive X-ray spectroscopy were used to confirm the AgNPs formation and their biophysical characterization. The larvicidal and pupicidal toxicity of AsEO, PcEO and biosynthesized AgNPs were evaluated against larvae and pupae of the dengue and Zika virus vector Aedes albopictus. Compared to the tested essential oils, the biofabricated AgNPs showed the highest toxicity against larvae and pupae of Ae.albopictus. In particular, the LC50 values of AsEO ranged from 44.23 (I) to 166 (pupae), LC50 values of PcEO ranged from 32.49 (I) to 90.05(IV), LC50 values of AsEO-AgNPs from 0.81 (I) to 1.12 (IV) and LC50 values of PcEO-AgPNs from 0.85 (I) to 1.19 (IV). Furthermore, histological analysis of the midgut cells of the control and treated larvae exhibited that the epithelial cells and brush border were highly affected by the fabricated AgNPs compared to the essential oils (AsEO and PcEO). Overall, the A. sinensis and P. cablin essential oils fabricated AgNPs have a potential of application as a biopesticide for mosquito control through safer and cost-effective approach.